2017
DOI: 10.1248/bpb.b17-00319
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Laser-Induced Choroidal Neovascularization by Hematoporphyrin Dimethylether-Mediated Photodynamic Therapy in Rats

Abstract: This study aimed to investigate the effect of hematoporphyrin dimethylether (HDME)-mediated photodynamic therapy for laser-induced choroidal neovascularization (CNV) in adult Brown Norway rats. HDME was administered via tail vein at 14 d after the laser photocoagulation, and the rats received irradiance with a laser light at 570 nm at 15 min after injection. CNV was evaluated by fundus photography, fundus fluorescein angiography, optical coherence tomography, and hematoxylin and eosin staining. We found that C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Laser irradiation destroys or induces necrosis in retinal cells including RPE cells [49] and therefore likely results in the exposure of remaining intact RPE cells to the contents of necrotic cells. Several cytokines such as IL-6, IL-8, and monocyte chemoattractant protein–1 have been implicated in CNV [50, 51], and we previously showed that NLR contains these cytokines [16].…”
Section: Resultsmentioning
confidence: 99%
“…Laser irradiation destroys or induces necrosis in retinal cells including RPE cells [49] and therefore likely results in the exposure of remaining intact RPE cells to the contents of necrotic cells. Several cytokines such as IL-6, IL-8, and monocyte chemoattractant protein–1 have been implicated in CNV [50, 51], and we previously showed that NLR contains these cytokines [16].…”
Section: Resultsmentioning
confidence: 99%
“…e oligomer consists of unsymmetrical metal-dielectric (Au/Si) nm, and this hybrid nanoparticle oligomer can be fine-tuned by fs laser-induced fusion of nanoscale gold nm to achieve Fano resistance [3]. Yan et al [4] research was designed to examine the impact of hematoporphyrin dimethyl ether (HDME)-mediated photodynamic treatment on laser-induced plexiform choroidal neovascularization (CNV) in mature Brown Norway mice [4]. Laser-induced fluorescence spectroscopy has the characteristics of high sensitivity, and fast and accurate monitoring.…”
Section: Related Workmentioning
confidence: 99%